Characterizing preclinical sub‐phenotypic models of acute respiratory distress syndrome: An experimental ovine study. Issue 19 (7th October 2021) - Millar, Jonathan E.; Wildi, Karin; Bartnikowski, Nicole; Bouquet, Mahe; Hyslop, Kieran; Passmore, Margaret R.; Ki, Katrina K.; See Hoe, Louise E.; Obonyo, Nchafatso G.; Neyton, Lucile; Pedersen, Sanne; Rozencwajg, Sacha; et al.
Abstract: The acute respiratory distress syndrome (ARDS) describes a heterogenous population of patients with acute severe respiratory failure. However, contemporary advances have begun to identify distinct sub‐phenotypes that exist within its broader envelope. These sub‐phenotypes have varied outcomes and respond differently to several previously studied interventions. A more precise understanding of their pathobiology and an ability to prospectively identify them, may allow for the development of precision therapies in ARDS. Historically, animal models have played a key role in translational research, although few studies have so far assessed either the ability of animal models to replicate these sub‐phenotypes or investigated the presence of sub‐phenotypes within animal models. Here, in three ovine models of ARDS, using combinations of oleic acid and intravenous, or intratracheal lipopolysaccharide, we investigated the presence of sub‐phenotypes which qualitatively resemble those found in clinical cohorts. Principal Component Analysis and partitional clustering identified two clusters, differentiated by markers of shock, inflammation, and lung injury. This study provides a first exploration of ARDS phenotypes in preclinical models and suggests a methodology for investigating this phenomenon in future studies. Abstract : This study provides a first exploration of ARDS phenotypes in preclinical models and suggests a methodology for investigating this phenomenon in future studies